Smoking cessation advice: the self-reported attitudes and practice of primary health care physicians in a military community, central Saudi Arabia - AlAteeq, Mohammed (2016)
Background Brief advice on smoking cessation from primary health care (PHC) physicians reduces smoking prevalence. However, few studies have investigated the provision of such advice by PHC physicians providing services to military communities. The aim of this study was to evaluate PHC physicians’ attitudes toward and practice of delivering smoking cessation advice to smokers in a military community in central Saudi Arabia. Methods A self-reported survey of PHC physicians was conducted in 2015 using a previously validated tool. The age, sex, educational level, job title, experience and previous smoking cessation training of each physician was recorded. Attitude (ten statements) and practice (six statements) were evaluated on a five-point Likert scale. Scoring system was applied and percentage mean scores (PMS) were calculated. Descriptive/statistical analyses were applied to identify factors that were significantly associated with a positive attitude and favorable practice (PMS >65 each). P-values <0.05 were considered to be significant. Results Response rate was 73/150 (48.6%), of which equal sex distribution (52%:48%) was observed, with a mean age of 35.3±9.6 years. General practitioners constituted 71.4%, followed by consultants (17.9%) and specialists (10.7%). Those with a postgraduate education formed 49.3%, while experience averaged 9.5±9.2 years. Approximately 56% had not attended a smoking cessation educational program in the previous year. Approximately 75% of physicians had a positive attitude (PMS =72.4±11.2), while 64.4% reported favorable practice (PMS =65.3±27.7). Higher education levels were significantly more associated with positive attitude than lower education levels (adj. odds ratio [OR] 95% confidence interval [CI] =17.9 [1.3–242.3]; adj. P=0.03). More experienced physicians (adj. OR [95% CI] =9.5 [1.6–54.6]) and those with positive attitude (adj. OR [95% CI] =6.1 [1.6–23.3]) were more likely to report a favorable practice, compared to the less experienced (adj. P=0.012) and physicians with a negative attitude (adj. P=0.008). Conclusion Provision of smoking cessation advice by primary health care physicians serving a military community is significantly associated with their attitude and years of experience. Patients who are seeking smoking cessation advice should be referred to physicians with higher levels of education. Routinely scheduled training on proper delivery of smoking cessation advice may increase physicians’ confidence; improve their attitude, and subsequently, their practice.